Social Conflicts and Citizenship in the Context of Societal Complexity - Leonardi, Laura (SocietàMutamentoPolitica, 2023)
This article addresses the issue of the legal expansion of citizenship in the context of increasing societal complexity. Social conflict has historically played a driving role in the enlargement of citizenship, but in the current phase it no longer seems to fulfil this function. The contribution aims to reflect on the conceptual tools needed to analyse social conflict related to the emergence of new forms of citizenship at a global scale. In the first part of this article, I focus on the inadequacy of classical analytical tools for the study of social conflict and the desirability of expanding the sociological canon with new concepts including its relation to social change. In the second part, I put forward the proposal to use some analytical tools – in particular the concepts of ius nexi, scale and lateral oscillation – to reconnect social conflict and the expansion of citizenship in social and legal terms.